Analyzing Astra Michael D Ruslim Education Foundation-SMK Negeri 2 Donorojo Pacitan collaboration model - Nurhayati, Indiyah; Hariadi, Eko; Suhartini, Ratna (Indonesian Journal of Multidisciplinary Science, 2024)
This study discusses the collaboration between SMK Negeri 2 Donorojo and Astra Michael D Ruslim Education Foundation (YPA MDR) in Corporate Social Responsibility (CSR). The method used is descriptive qualitative, involving researchers as participants who collect data through interviews, observation, documentation, and Focus Group Discussion (FGD). This cooperation is based on legal basis, including the Limited Liability Company Law and the results of coordination meetings with the Pacitan District Education Office. The parties involved include YPA MDR and SMK Negeri 2 Donorojo. The objectives of the cooperation involve improving access and quality of education, community empowerment, creating community involvement, and improving the quality of the workforce. The benefits include improving the company's image, the quality of the company's human resources, and compliance with government regulations. The research concludes that this cooperation has a legal basis, clear objectives, significant benefits, and good governance.